The Jurisprudence Sentence for Euthanasia - Mohammad Rahmani; Nafiseh Zarvandi; Morteza Abdoljabari (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective:Today, instead of preserving the health and life of people in some health centers, under the pretext of pity, the patients with difficult-to-cure diseases are suggested to accelerate selective death. Euthanasia dates back to ancient Roma and is one of the controversial topics discussed in different legal and jurisprudential aspects in academic circles. With the intent of explaining the jurisprudence sentence for euthanasia, alongside proposing some primary topics, in this article we have tried to introduce a new category based on an effective criterion in the jurisprudence sentence unlike the common categories in scientific circles. Method: This library research is descriptive-analytical for which the articles of years between 1996 and 1997 were studied and reviewed. The procedure was as follows: keywords such as euthanasia, self-killing, retaliation, suicide, self-preservation, and imperative and dispositive rule were searched; then, the Qur`an and the books with jurisprudential and deductive themes such as Fikh va Hoghoogh-e- Tahaffozi by Ayat-Allah Sistani, Vasael Al-Shiea and Mostadrak were used. After analysis, the findings were taught and discussed in 10 sessions of the Hawza classes. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The overall eight types of euthanasia and their subcategories are classified into three general major categories: a) Three of them are the case of intentional murdering and imperative rule of prohibition as well as dispositive rule of retaliation. b) One of them is the case of general suicidal that has only imperative prohibition. c) Four of them are the case of general necessity of self-preservation, leaving which has imperative prohibition, and doesn`t have dispositive rule due to self-killing. Conclusion:All of the eight forms of euthanasia are prohibited and we recommend that instead of this, revival be tried. This requires conducting studies to find treatment for difficult-to-cure diseases.For downloading the full-text of this article please click here.